Theoretical study of edge states in BC(2)N nanoribbons with zigzag edges - Harigaya, Kikuo (Springer, 2013)
In this paper, electronic properties of BC(2)N nanoribbons with zigzag edges are studied theoretically using a tight binding model and the first-principles calculations based on the density functional theories. The zigzag BC(2)N nanoribbons have the flat bands when the atoms are arranged as B-C-N-C along the zigzag lines. In this arrangement, the effect of charge transfer is averaged since B and N atoms are doped in same sublattice sites. This effect is important for not only the formation of flat bands but also for the validity of the tight binding model for such system.